KAJIAN FEMINISME DALAM NOVEL INDONESIA DAN NOVEL TERJEMAHAN: STUDI PERBANDINGAN TOKOH PEREMPUAN DALAM NOVEL: STUDI PERBANDINGAN TOKOH PEREMPUAN DALAM NOVEL - yenimarlina yenimarlina; Asep Saefurohman; Ece Sukmana (Universitas Muria Kudus, 2026)
This study aims to analyze the construction of subject and object positions of female characters, identify the positioning of readers, and compare the contrast of feminist ideologies in the novels Saman by Ayu Utami and Perempuan di Titik Nol by Nawal El Saadwi through the perspective of Sara Mills' feminist critical discourse analysis. This research employed a qualitative approach with a descriptive-comparative method. The data sources consisted of the novels Saman and Perempuan di Titik Nol. Data collection techniques were conducted through documentation studies using close reading and note-taking methods. Data analysis was carried out through structural data reduction, Sara Mills' textual analysis, cross-cultural comparison, and drawing conclusions. The findings reveal that both novels successfully deconstruct the position of women from passive objects into subjects who possess linguistic authority and agency in resisting patriarchy. Female characters in Saman are constructed as plural and autonomous subjects fighting for bodily rights and individual freedom (characteristics of liberal feminism), whereas the character of Firdaus in Perempuan di Titik Nol transforms into a solitary liberated subject after experiencing extreme structural violence (characteristics of radical feminism). The similarity between the two novels lies in their rejection of gender subordination, while the difference manifests in the resistance strategies shaped by the socio-cultural spaces of Indonesia and Egypt. The findings of this study have implications as alternative literary teaching materials in senior high schools to foster students' critical literacy and gender equality in accordance with the demands of the Independent Curriculum (Kurikulum Merdeka).